Evaluating the expression is determined by using Euler's theorem
color(blue)(e^(ix)=cosx+isinx)eix=cosx+isinx
e^(11pi/6i)=color(blue)(cos(11pi/6)+isin(11pi/6)e11π6i=cos(11π6)+isin(11π6)
e^(11pi/6i)=cos((12pi)/6-pi/6)+isin((12pi)/6-pi/6)e11π6i=cos(12π6−π6)+isin(12π6−π6)
e^(11pi/6i)=cos(2pi-pi/6)+isin(2pi-pi/6)e11π6i=cos(2π−π6)+isin(2π−π6)
e^(11pi/6i)=cos(-pi/6)+isin(-pi/6)e11π6i=cos(−π6)+isin(−π6)
Applying the trigonometric identities:
color(green)(cos(-alpha)=cosalpha)cos(−α)=cosα
color(green)(sin(-alpha)=-sinalpha)sin(−α)=−sinα
Let us continue computing e^((11pi)/6)e11π6
e^(11pi/6i)=cos(-pi/6)+isin(-pi/6)e11π6i=cos(−π6)+isin(−π6)
e^(11pi/6i)=color(green)(cos(pi/6))color(green)(-isin(pi/6))e11π6i=cos(π6)−isin(π6)
e^(11pi/6i)=sqrt3/2-i1/2e11π6i=√32−i12
Let us compute e^((17pi)/12i)e17π12i
e^((17pi)/12i)=color(blue)(cos((17pi)/12)+isin((17pi)/12)e17π12i=cos(17π12)+isin(17π12)
e^((17pi)/12i)=cos((12pi)/12+(5pi)/12)+isin((12pi)/12+(5pi)/12)e17π12i=cos(12π12+5π12)+isin(12π12+5π12)
e^((17pi)/12i)=cos(pi+(5pi)/12)+isin(pi+(5pi)/12)e17π12i=cos(π+5π12)+isin(π+5π12)
Applying the trigonometric identities
color(brown)(cos(pi+alpha)=-cosalpha)cos(π+α)=−cosα
color(brown)(sin(pi+alpha)=-sinalpha)sin(π+α)=−sinα
Let us continue computing e^((17pi)/12i)e17π12i
e^((17pi)/12i)=cos(pi+(5pi)/12)+isin(pi+(5pi)/12)e17π12i=cos(π+5π12)+isin(π+5π12)
e^((17pi)/12i)=color(brown)(-cos((5pi)/12)color(brown)-isin((5pi)/12)e17π12i=−cos(5π12)−isin(5π12)
e^((17pi)/12i)=-(sqrt6-sqrt2)/4-i(sqrt2+sqrt6)/4e17π12i=−√6−√24−i√2+√64
e^((17pi)/12i)=(-sqrt6+sqrt2)/4-i(sqrt2+sqrt6)/4e17π12i=−√6+√24−i√2+√64
hint:To evaluate cos((5pi)/12) and sin((5pi)/12)cos(5π12)andsin(5π12)
cos((5pi)/12)=cos(pi/6+pi/4)cos(5π12)=cos(π6+π4)
sin((5pi)/12)=sin(pi/6+pi/4)sin(5π12)=sin(π6+π4)
So,
color(blue)(e^(11pi/6i)-e^((17pi)/12i)e11π6i−e17π12i
=sqrt3/2-i1/2-((-sqrt6+sqrt2)/4-i(sqrt2+sqrt6)/4)=√32−i12−(−√6+√24−i√2+√64)
=sqrt3/2-i1/2-((-sqrt6+sqrt2)/4)+i(sqrt2+sqrt6)/4=√32−i12−(−√6+√24)+i√2+√64
=sqrt3/2-i1/2+sqrt6/4-sqrt2/4+i(sqrt2+sqrt6)/4=√32−i12+√64−√24+i√2+√64
=(2sqrt3)/4-(2i)/4+sqrt6/4-sqrt2/4+i(sqrt2+sqrt6)/4=2√34−2i4+√64−√24+i√2+√64
=(2sqrt3)/4+sqrt6/4-sqrt2/4+i(sqrt2+sqrt6)/4-(2i)/4=2√34+√64−√24+i√2+√64−2i4
=(2sqrt3+sqrt6-sqrt2)/4+i(sqrt2+sqrt6-2)/4=2√3+√6−√24+i√2+√6−24